Question of swimmers' training in modern foreign literature on sport of high performances - Kachurovs'kyy, D. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose: Opinions of the foreign authors about modern world outlook and moral training of the swimmers are examined. Recommendations regarding improving of training of Ukrainian swimmers are given.